PENGETAHUAN REMAJA TENTANG PENDIDIKAN SEKS DENGAN SIKAP TERHADAP ABORSI - Sriami .; Evi Yunita Nugrahini; Paryanti . (JURNAL PENELITIAN KESEHATAN, 2016)
Abortion (abortion) is prohibited by law, but in fact there are 2.3 million women have abortions(Kompas, 3 March 2000). Data WHO says, 15% to 50% of maternal deaths caused by unsafeabortion. This research is analytic cross sectional. Samples were taken by simple random samplingof 150 respondents. The independent variable is knowledge tentan sex education, while thedependent variable is the attitude towards abortion. Using data collection questionnaire. To analyzethe relationship by using tables. Research shows that almost all have less knowledge as many as61.33% of respondents, and most have a positive attitude, an attitude that rejects the existence ofsborsi ie 54.67% of the respondents. Based on this study it can be concluded that the knowledgeof adolescents about sex education has nothing to do with adolescent attitudes toward abortion. Inthis case the gesture may also be influenced by personal experience, the influence of other people,culture, mass media, religion, and emotional factors.